A Case of Annular Elastolytic Giant Cell Granuloma Associated with Syphilis - Xiaoping Liu; Wei Zhang; Yeqiang Liu; Mingyuan Xu (Karger Publishers, 2018)
Annular elastolytic giant cell granuloma (AEGCG) is a rare granulomatous skin disease characterized by annular patches with slightly raised borders, hypopigmented and/or atrophic centers found mainly on sun-exposed skin. Histologically, it is characterized by phagocytosis of elastic fibers by multinucleated giant cells. The pathogenesis of the disease is unclear. We report a case of 55-year-old man with AEGCG in association with syphilis, whose condition improved when hydroxychloroquine sulfate and topical tacrolimus were administered over a 2-month period.